Criteria for Adaptive Reuse of Heritage Shop Houses Towards Sustainable Urban Development - Mohd Abdullah, Muhamad Shahril; Suratkon, Azeanita; Syed Mohamad, Syed Burhanuddin Hilmi (International Journal of Sustainable Construction Engineering and Technology, 2020)
Pre-war shop houses in some town areas of Malaysia are among national heritage buildings that require conservation efforts through adaptive reuse. Adaptive reuse, in line with sustainability principles, is a process of revitalising or reinventing disused or ineffective existing buildings (including old or historical buildings) for new use, purpose or function. This paper provides a discussion on the criteria of adaptive reuse potential (ARP) for existing and heritage buildings that can be applied for the old shop houses. The criteria are classified into six aspects: economic, environment, social, architecture, technology, and legislative. With the intention to contribute to the attempts of ensuring that pre-war shop houses can be conserved in a sustainable manner, a list of the criteria is used, and further studies are proposed to develop a decision-making methodology that will be useful for key parties: owners, the government and architects (conservation specialist leaders). This will facilitate the determination for the adaptive reuse of potential buildings, as well as possible alternatives (new functions)